MADRASAH CURRICULUM MANAGEMENT - Muzakki, Ahmad; Hefniy, Hefniy; Aisyah, Nur; Jazilurrahman, Jazilurrahman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The rapid development of technology causes a shift in morals, and children are very easily influenced by negative behavior. Religious education is an effort to protect children from being affected by behavior prohibited by religion. Implementing religious education is always linked to madrasas and Islamic boarding schools, which are the key to children's success in balancing the goals of this world and the hereafter. Madrasas and Islamic boarding schools should be integrated into an institution so that learning can be fully formed to form reasonable minds and morals. Therefore, this article describes the management of the Islamic boarding school-based madrasah curriculum, in which case MA Nurul Qur'an Patokan Kraksaan is the object of the research study. The focus of the study is the planning, implementation, organization, and evaluation of the madrasa curriculum. Through interview observations and documentation, it was found that MA Nurul Qur'an Patokan Kraksaan carries out madrasa curriculum management integrated with well-managed Islamic boarding schools.